The Impact of Leadership Styles, Organizational Culture, and Innovation on School Performance in Private Educational Institutions in Bogor City - Tarigan, Budi Akhmad; Marnoto, Marnoto; Anwar, Syamsul; Yusda, Desi Derina (PT. BATARI EDU CALYA, 2024)
This study examines the impact of leadership styles, organizational culture, and innovation on the performance of private educational institutions in Bogor City. A quantitative research design was employed, collecting data from 150 respondents using structured questionnaires. The analysis involved descriptive statistics, correlation, multiple regression, and moderation analysis. The results indicate that transformational leadership, organizational culture, and innovation significantly contribute to school performance, with innovation being the strongest predictor. Furthermore, the study finds that a strong organizational culture amplifies the positive effects of transformational leadership. These findings highlight the critical roles of leadership, culture, and innovation in enhancing the performance of private schools. The study provides valuable insights for school leaders and policymakers seeking to improve educational outcomes in private institutions.